Legal Aspects of Save-Loan Business Activities Agreement at Sejahtera Saving-Loans Cooperatives, Pasir Jambu District, Bandung, West Java - Otom Mustomi; Raihan Raihan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The legal aspects of the agreement in the savings and loan business activities of the Sejahtera Pasir Jambu Savings and Loan Cooperative (Koperasi Simpan Pinjam). The problem in this research is how the legal aspects of the agreement in the savings and loan cooperative activities are, and how the study of the position of the Prosperous Savings and Loans Cooperative in the event of a default. In this study, the method used was the empirical normative legal research method, namely research conducted by conducting secondary research first and then proceeding with researching primary data in the field. Empirical normative is also research that examines the implementation or implementation of positive legal provisions factually in each particular legal event. The study aims to ascertain whether the results of the application of the legal event are following the provisions of the legislation. So, this research needs secondary data and primary data. Based on the results of the study, it is known that the Pasir Jambu Prosperous Savings and Loans Cooperative is not yet a legal entity, the savings and loan agreement is made by applying and will be assessed for feasibility by the Pasir Jambu Prosperous Savings and Loans Cooperative if it is deemed feasible, the signing of the credit agreement will immediately be carried out. The conclusion of the problem faced by the Cooperative Savings and Loans Cooperative Sejahtera Pasir Jambu is the occurrence of bad loans. The written agreement is intended as evidence in the event of a dispute. Although for certain agreements, if the written form cannot be carried out, the agreement is invalid, then the form of an agreement made by the Sejahtera Savings and Loans Cooperative is following the applicable provisions.